MELOLONTHIDAE ASSOCIADOS A PLANTAS DE PITAYA NO CERRADO-PANTANAL - ALVES, Elizandra Goulart Jacques; ZAZYCKI, Luiza Cristiane Fialho; SILVA, José Victor; PRADO, Deyvid Martins do; SILVA, Daniel Lima da; SILVA, Adriana de Castro Correia da (ANAIS DO ENIC, 2023)
-